L1 Input-Output Finite-Time Control of Positive Switched Nonlinear Systems. (7th August 2019) - Liu, Leipo; Cao, Xiangyang; Fan, Bo; Fu, Zhumu
Abstract : In this paper, the problem ofL 1 input-output finite-time control of positive switched nonlinear systems with time-varying and distributed delays is investigated. Nonlinear functions considered in this paper are located in a sector field. Firstly, the proof of the positivity of switched positive nonlinear systems with time-varying and distributed delays is given, and the concept ofL 1 input-output finite-time stability (L 1 IO-FTS) is firstly introduced. Then, by constructing multiple co-positive-type nonlinear Lyapunov functions and using the average dwell time (ADT) approach, a state feedback controller is designed and sufficient conditions are derived to guarantee the corresponding closed-loop system isL 1 IO-FTS. Such conditions can be easily solved by linear programming. Finally, a numerical example is provided to demonstrate the effectiveness of the proposed method.